Lellarap, desarrollo de una aplicación de pausas activas como apoyo a la salud psicológica de las personas (2021)
As shown in several studies, in current times and as a result of confinement and remote work, employees and people in general are often overwhelmed in their homes. That is the reason for proposing the creation of an application that serves as support for all those who wish to improve their physical, mental and personal health. This application will be created under the Waterfall model development methodology, and is precisely aimed at solving the problem of Physical and Psychological wear caused by confinement or generalized stress. Using dynamic tools such as active breaks, hobbies, activities, readings and advice, and visualization of the mental state, all linked to the needs and personalization of the user, defined by the Software for his mental health, the intention is that the application for each user should be unique respecting his privacy and keeping sensitive information within a database of local data.